Studying the conditions of emulsions formation with the use of the theory of formal analogy of processes - Yu. A. Taran; T. I. Pynkova; A. L. Taran (Тонкие химические технологии, 2013)
The article shows the possibility of using formal analogy of processes with restructuring of the original system to calculate the main parameters of self-dispersion: interfacial tension at the interface and the drops radius of the formed emulsion.